2020
DOI: 10.33377/jkh.v4i1.67
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Qigong Exercise Selama Kehamilan dalam Pencegahan Gejala Depresi Post Partum pada Ibu Remaja

Abstract: Salah satu permasalahan yang dijumpai pada seorang wanita setelah melahirkan adalah depresi postparum. Masalah ini harus diatasi melalui intervensi keperawatan dalam meningkatkan kesehatan ibu dan bayi salah satunya melalui qigong exercise. Tujuan penelitian ini adalah untuk mengidentifikasi efektifitas qigong exercise dalam pencegahan gejala depresi postpartum pada ibu remaja. Penelitian quasi eksperimen ini menggunakan teknik purposive sampling dengan 27 responden ibu remaja. Alat ukur yang digunakan adalah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Factors causing postpartum depression cover biological factors, characteristics, and background of the mother (Puspasari & Fanani, 2020). Levels of estrogen (estradiol and estriol), progesterone, prolactin, and cortisol which increase and decrease too quickly or too slowly are biological factors causing PPD (Karl et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors causing postpartum depression cover biological factors, characteristics, and background of the mother (Puspasari & Fanani, 2020). Levels of estrogen (estradiol and estriol), progesterone, prolactin, and cortisol which increase and decrease too quickly or too slowly are biological factors causing PPD (Karl et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that is not related to the incidence of postpartum depression is education (Firmin et al, 2019). Studies showed that although most of the respondents have a high level of education, they can still be at risk for postpartum depression (Puspasari & Fanani, 2020). Hutagaol (2010), revealed that mothers with higher education generally have feelings of ambivalence between their role as mothers in caring for children and their families and their desire to improve their careers so that they are more vulnerable to experiencing depression (Arimurti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sports exercises carried out in the prenatal period are able to prevent the occurrence of postpartum blues or baby blues syndrome. These exercises include Qigong movement exercises that focus on slow body movements and body balance with a combination of subtle breathing techniques, so as to reduce stress levels associated with the psychological condition of the mother after giving birth [16]. The sports concept in the form of Low, Moderate to Virgous Physical Activity was chosen as an intervention in the study (n=5).…”
Section: Types Of Exercise In Baby Blues Syndromementioning
confidence: 99%